EFFECTS OF RESIDUAL CONFIGURATION ON THE RATE OF TRICHLOROETHYLENE (TCE) DISSOLUTION - GONULLU, MT; FARQUHAR, GJ (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
In order to examine the effects of trichloroethylene (TCE) residual configuration on the TCE dissolution, four different runs are carried out. For these purposes, TCE volumes of 10 and 25 ml are spread over the sand column during packing, or put in the bottom of the bottle before packing the sand. Soil flushing performed by distilled water injection at a specific discharge of 5.8 x 10(-3) cm/s showed that the residual amount of Dense Non-Aqueous Phase Liquid (DNAPL) plays a much greater role on the rate of dissolution. The effect of configurations in the sand column of DNAPL such as ponded residual and spread residual are then studied, and higher concentrations for spread residual are obtained for longer.
Keywords: DENSE NONAQUEOUS PHASE LIQUID (DNAPL); TRICHLOROETHYLENE (TCE); DISSOLUTION; POROUS MEDIA; GROUNDWATER; RESIDUAL CONFIGURATION; MAXIMUM CONCENTRATION; Engineering; Environmental Sciences & Ecology; Water Resources